A Multicentric Prospective Study on Maxillofacial Trauma Due to Road Traffic Accidents: The World Oral and Maxillofacial Trauma Project. Issue 4 (16th June 2022) - Romeo, Irene; Roccia, Fabio; Aladelusi, Timothy; Rae, Euan; Laverick, Sean; Ganasouli, Dimitra; Zanakis, Stelios N.; de Oliveira Gorla, Luis Fernando; Pereira-Filho, Valfrido Antonio; Gallafassi, Daniel; Faverani, Leonardo Perez; Alalawy, Haider; et al.
Abstract : Abstract: The purpose of this prospective multicenter study was to analyze the epidemiology, patterns, and management of maxillofacial fractures due to road traffic accidents (RTAs) worldwide. Between Monday September 30, 2019 and Sunday October 4, 2020, 1066 patients with RTAs related fractures were admitted to 14 maxillofacial surgery departments. The following data were analyzed: age, gender, mechanism of injury, alcohol or drug abuse at the time of trauma, maxillofacial fracture site, facial injury severity scale (FISS) score, associated injuries, day and month of trauma, time of treatment, type of treatment and length of hospital stay. Data were analyzed using bivaried and multivaried statistical analysis. Eight hundred seventy patients were male, and 196 were female. The most common mechanism of injury was motorcycle accidents (48%). More than half of the patients had fractures of the middle third of the maxillofacial skeleton. In total, 59% of the study sample underwent open reduction internal fixation. The median facial injury severity scale (3 points) and the medial hospital stay (3 days) were significantly lower in patients with seatbelts and helmet (P   <  0.001). This first prospective, multicenter epidemiological study shows that motorcycle accidents are the leading cause of RTAs related fractures, mostly in young males. Particularly in Australia and Europe, the incidence of RTAs was significantly lower. Moreover, this study found that the severity of maxillofacial lesions was significantly higher in patients without safety devices, with consequent longer hospital stay demonstrating the efficacy of road safety policies in preventing maxillofacial injury.